LEGAL MECHANISMS TO ENSURE SECURITY OF ENTREPRENEURSHIP (AVIATION ASPECT) - Bezzubov, Dmitriy; Yeryashov, Yevgen (Proceedings of National Aviation University, 2018)
Purpose: the purpose of our research is an analysis of existing threats, dangers and challenges of entrepreneurship in conditions of the present and the formulation of the basic foundations for forming methods of ensuring the legal security of enterprises of transport sphere. Determine а place and role of enterprise security businesses and legal mechanisms of its provision Methods: using the comparative method of scientific knowledge revealed major threats in entrepreneurship and basic provisions for legal mechanisms to ensure the security of enterprises through the definition of an administrative method Regulation of legal relations. Results: the problem of business security companies is determined through the teachings of administrative, air, space law and application of the achievements science of economics and management. Each of the sciences forms an interdisciplinary approach to the question of business security in the system of modern economic and legal relations. In the modern economic system security problem business formed through the activity of the State and the possibilities of intervention in the activities of the economic entities of the transport sector. Definition of business security companies in the General Security is due to the presence of the following legal factors and mechanisms: а) a market economy based on competition, is a very dynamic system, and thus very dangerous; b) the Ukrainian market is at a stage of formation and mechanisms are not yet spent; с) in the country the missing steel standards rights protect the interests of entrepreneurs. In fact, business security is formed through a combination of economic, legal and social factors of its provision. Discussion: in this article author offers basic provisions regarding the legal mechanisms providing entrepreneurship.